Modern electrochemical processes and technologies in ionic melts - Omelchuk A.; Volkov S.V.; Zarubitskii O.G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
An analysis of the known methods for the electrochemical purification of non-ferrous metals in ionic melts is presented. A comparative estimation of the results of the electrochemical purification of non-ferrous metals by different methods has been performed. The main regularities of the electrochemical behavior of non-ferrous metals in conventional and electrode micro-spacing electrolysis are presented. It has been found that when electrolyzing some metals, e. g. bismuth, gallium, there is either no mass exchange between the electrodes, or it occurs under filtration conditions. It has been shown that the electrode micro-spacing processes provide a high quality of non-ferrous metals purification at low specific consumption of electric power and reagents. The use of bipolar electrodes and β-alumina diaphragms hinders the transfer of metallic impurities from the anode to the cathode. The effects revealed were used to develop new processes for the separation of non-ferrous metal alloys in ionic melts; most of them have been put into practice in non-ferrous metallurgy.